Pufferfish optimization algorithm: A bioinspired optimizer - Catalbas, Mehmet Cem; Gulten, Arif (wiley, 2022)
In this work, a completely innovative meta-heuristic optimization algorithm is proposed. This new meta-heuristic optimization method was inspired by the circular structures on the seafloor which are created by one of the pufferfish species which is called as Torquigener albomaculosus. The basic parameters of the inventive method were determined by the parameters observed during the process of the circular structure of the pufferfish. The process of performing this natural phenomenon has been detailed in this work. In addition, detailed information about the concept of optimization, development process, and activity areas are given in the study. Information about the general terms that constitute the concept of meta-heuristic optimization are given in this work, and the meta-heuristic optimization methods which are widely used in the literature are explained. The performance of this proposed method which is inspired by nature has been compared with other methods used extensively in the literature. © 2022 Scrivener Publishing LLC.
Keywords: Bio-inspired optimization; Mathematical modeling; Meta-heuristic; Optimization; Torquigener albomaculosus